Integrated Cost Allocation of Transmission Usage under Electricity Markets - Hermagasantos Zein; Ignatius Riyadi Mardiyanto; Ali Mashar (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2012)
Cost allocation of transmission usage on the power networks is an important issue especially in the modern electricity market mechanism. In this context, all costs that have been embedded in the transmission, embedded cost, should be covered by the transmission users. This paper follows general methods, where generators are fully responsible to cover the embedded cost. It proposes a method to determine the cost allocation of transmission usage based on decomposition through the superposition techinique to determine power flow contributions from an integrated base case of the results of the power flow calculations of all transactions, bilateral and nonbilateral contracts. Mathematically, the applied formulations are illustrated clearly in this paper. The proposed method has been tested with 5-bus system and the results are much different compared to a few of the published methods. This is shown by the test results on the 5 bus system. The published methods produce total power flow contributions in each line is greater than the actual. And they earn total revenues approximately 11.6% greater than the embedded cost. While on the proposed method, the power flow contributions are equal to the actual and the revenues are equal to the embedded cost. It shows also that the proposed method gives results as expected